GASTRIC CONDITION IN CRITICALLY ILL PATIENTS ON ARTIFICIAL VENTILATION (Conferencea, 2024)
The condition of the gastrointestinal tract (GIT) in critically ill patients undergoing mechanical ventilation (MV) is associated with a high risk of developing severe complications. These complications include erosive and ulcerative lesions, gastrointestinal bleeding, acute pancreatitis, stress-induced gastropathy, and ischemic damage to the gastrointestinal mucosa. The main factors contributing to the development of these disorders include stress reactions of the body, ischemic changes, infections, and the effects of pharmacological agents used in the intensive care of the underlying disease. Long-term mechanical ventilation further worsens the condition of the gastrointestinal tissues, reducing their perfusion and disrupting the protective functions of the mucosa. An important aspect of pathogenesis is impaired microcirculation and hypoxic damage, which contributes to increased permeability of the mucosa and an increased likelihood of systemic inflammatory reactions. This article discusses the features of the GIT condition in this category of patients, as well as analyzes risk factors and suggests possible strategies for preventing these complications.